SOX30 Overexpression Reflects Tumor Invasive Degree, Lymph Node Metastasis and Predicts Better Survival in Colorectal Cancer Patients: A Long-Term Follow-Up Cohort Study - Li, Chao; Li, Pengfei; Yu, Lulu; Sun, Qingsen; Gu, Bin; Sun, Yanhua; Sun, Liansheng (Frontiers in Surgery, 2022)
Aims: Sex-determining region Y-box containing gene 30 (SOX30) takes part in the progression of several cancers, while its clinical engagement in colorectal cancer (CRC) is obscure. Therefore, this study aimed to explore the association of SOX30 with clinicopathological features and prognosis in CRC patients. Methods: Tumor and adjacent noncancerous specimens of 195 CRC patients who received resection were acquired. Furthermore, an immunohistochemistry assay was performed to detect SOX30 protein expression in these specimens; meanwhile, SOX30 mRNA expression was determined by reverse transcription-quantitative polymerase chain reaction assay in 95 out of 195 specimens. Moreover, clinical characteristics and survival data (follow-up duration median (range): 71.0 (7.0-95.0) months) of CRC patients were gathered. Results: SOX30 protein and mRNA expressions were both decreased in CRC tumor tissue compared to adjacent tissue (both P<0.001). Furthermore, a negative correlation was found in tumor SOX30 protein expression with tumor size (P=0.049), lymph node (LYN) metastasis (P=0.018), T stage (P=0.001), N stage (P=0.034), and TNM stage (P=0.001); tumor SOX30 mRNA expression was also negatively correlated with LYN metastasis (P=0.001), T stage (P=0.019), N stage (P=0.004), and TNM stage (P<0.001). Furthermore, tumor SOX30 protein expression was positively correlated with overall survival (OS) (P=0.017), while tumor SOX30 mRNA expression was not correlated with OS (P=0.070). Multivariate Cox’s regression analysis illustrated that tumor SOX30 protein high expression was an independent factor for favorable OS (hazard ratio: 0.525, P=0.034). Conclusions: SOX30 has potential as a biomarker for the progression and prognostication of CRC, which might improve the management of CRC.